Learning Analytics in Higher Education: A Case of the Netherlands - Asper Van Dijk (CV Edujavare Publishing, 2025)
Learning analytics has emerged as a transformative approach to enhancing educational quality and student success in higher education, with the Netherlands serving as a particularly instructive case of systematic implementation within a robust regulatory and collaborative framework. This study examines the adoption, development, and outcomes of learning analytics across Dutch universities, drawing upon institutional case studies, national policy frameworks, and empirical evidence from student-facing dashboard implementations. The Dutch approach is distinguished by its emphasis on responsible data use under the General Data Protection Regulation, the collaborative infrastructure provided by SURF—the national ICT cooperative for education and research—and the integration of learning analytics within a broader ecosystem of educational innovation. Key institutional developments include Utrecht University's centralised Learning Analytics team and community, Eindhoven University of Technology's self-regulated learning dashboard, and the Open University of the Netherlands' analytics-supported distance learning design. The research identifies four critical success factors: clear educational goal alignment, privacy-by-design principles, stakeholder-inclusive development processes, and phased implementation with comprehensive teacher support. Findings indicate that student-facing learning analytics, when designed with transparency and user agency, significantly improve self-regulated learning, academic writing skills, and early identification of at-risk students. However, persistent challenges include technical barriers in data extraction and visualisation, the need for enhanced data literacy among both students and educators, and the tension between institutional efficiency goals and individual student privacy. The study concludes that the Dutch model offers a replicable framework for ethically grounded, pedagogically informed learning analytics implementation, while highlighting the necessity of continuous evaluation and iterative improvement to realise the full potential of data-informed education.